Integration and utilization of e-learning: an approach to curriculum implementation in schools amidst Covid-19 pandemic - Msheliza, I. Adamu; Sabo , Umar; Lazarus , J. Goje (Kashere Journal of Education, 2023)
The aim of this study is to see in to the need for integrating and utilizing the E-learning platforms as an alternative means of curriculum implementation at the classroom level amidst COVID-19 pandemic and to a likely situation of similar effects henceforth. In spite of the numerous challenges hindering the implementation of the curriculum in our schools, it was therefore found that, the outbreak of Corona Virus Disease in 2019 has posed a great setback to effective curriculum implementation at the school level since the containment of community transmissions of the pandemic is achieved by a total closure of educational institutions among others. It is undoubtedly true that the Covid-19 pandemic has negatively impacted on the country’s educational system hence the forceful banned on social gathering which is very common and unavoidable to our traditional system of education in Nigeria and the country is lagging behind in terms of its capacity to switch to E-learning. Schooling system was suspended for a period of time which is against the claim that learning is a continuous process and should not be interrupted. It is therefore concluded that in spite of its disadvantages and some challenges as barriers to effective integration and utilization, E-learning remains the only alternative option to curriculum implementation amidst this kind of pandemic, which may lead to school closure similar to that of Covid-19 era.